Two shrines in front of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
This is a view of the west-facing elevations of the two shrines that stand in front of the Mahanaleshwar Temple. These temples are built in red sandstone, consisting of plain plinth mouldings, geometric motifs on the wall subsidiary projections, and deep niches in the principal projections. The shrines have a shekhari variety of shikharas (superstructures). The walls are bereft of any icons.